Plastic wrap combined with alcohol wiping is an effective method of preventing bacterial colonization on mobile phones. Issue 44 (30th October 2020) - Wu, Yen-Hung; Chen, Chao-Ju; Wu, Hsiu-Yueh; Chen, I; Chang, Yi-Hsuan; Yang, Pei-Hsuan; Wang, Tzu-Yi; Chen, Li-Chin; Liu, Kuan-Ting; Yeh, I-Jeng; Wu, Deng-Chyang; Hou, Ming-Feng; et al.
Abstract: Introduction: Using mobile phones for communication in emergency departments is a common practice; however, several studies have demonstrated that they may act as vectors for bacteria and viruses. This study evaluated the effectiveness of plastic wrapping in decreasing bacterial contamination on mobile phone surfaces. Method: We used culture dishes and a luminometer to detect bacterial colonies and contamination on the phone surfaces. Result: Our experiment showed that bacterial colonies exist on mobile phones before and after work. We found that wiping with 75% alcohol sanitizers effectively reduces the number of colonies on either a mobile phone or a temporary plastic covering. In addition, we found that bacterial colonies do not contaminate or adhere to plastic wrap any easier than to mobile phones. Conclusion: These results demonstrated the effectiveness of plastic wrap for protecting mobile phone surfaces against bacterial colonization. In addition, applying a layer of plastic wrap protects the phone from potential damage due to the alcohol.